JIHAD DAN ETIKA BERBANGSA DALAM MENANGGULANGI PAHAM RADIKALISME DAN TERORISME DALAM ISLAM - Arif Muzayin Shofwan (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
The term jihad, whether recognized or not, does exist in Islam. This qualitative descriptive paper, incorporating a literature review, discusses jihad and national ethics in combating radicalism and terrorism in Islam. The data analysis employed content analysis, sorting the data according to the research focus. This study concluded that true jihad is anything done sincerely to fight for Islamic teachings without resorting to violence (al-harb), except in emergencies. There are four areas where jihad should be conducted without bloodshed: education, economics, morals, and health. These four jihads should be a priority for Muslims living as a nation and sharing one homeland, Indonesia. Meanwhile, jihad in the sense of waging war (al-qital) can be undertaken in emergencies, as Islam prohibits killing people without justification; destroying property, homes, and public facilities; creating anxiety and fear in society; prohibiting denouncing each other as infidels; and prohibiting divisiveness.